PENGARUH LIKUIDITAS PROFITABILITAS DAN LEVERAGE TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Silaban, Rosi; Efriyenti, Dian (SCIENTIA JOURNAL, 2020)
The related dividend policy concerns the use of profits which are the rights of shareholders. The dividend payout policy can have such an important impact on investors and companies that will pay.This research was conducted with the aim to examine and further test the effect of current ratio, return on equity, and debt to equity ratio on dividend policy on manufacturing companies listed on the Indonesia Stock Exchange. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The sample selection technique in this study used a purposive sampling technique with certain criteria and 9 companies were included within a period of 5 years so that 45 samples were obtained. The data in this study are secondary data in the form of financial statements obtained through the Indonesia Stock Exchange and the company's website. The results showed that partially the current ratio had a significant positive effect on dividend policy, return on equity had a significant positive effect on dividend policy, and the debt to equity ratio had no significant effect on dividend policy. The results of the F test analysis show that the variable current ratio, return on equity, and debt to equity ratio together have a significant effect on dividend policy.